Temperature-Dependent Regulation of Proteostasis and Longevity - Vakkayil, Kavya Leo; Hoppe, Thorsten (Frontiers in Aging, 2022)
Temperature is an important environmental condition that determines the physiology and behavior of all organisms. Animals use different response strategies to adapt and survive fluctuations in ambient temperature. The hermaphrodite Caenorhabditis elegans has a well-studied neuronal network consisting of 302 neurons. The bilateral AFD neurons are the primary thermosensory neurons in the nematode. In addition to regulating thermosensitivity, AFD neurons also coordinate cellular stress responses through systemic mechanisms involving neuroendocrine signaling. Recent studies have examined the effects of temperature on altering various signaling pathways through specific gene expression programs that promote stress resistance and longevity. These studies challenge the proposed theories of temperature-dependent regulation of aging as a passive thermodynamic process. Instead, they provide evidence that aging is a well-defined genetic program. Loss of protein homeostasis (proteostasis) is one of the key hallmarks of aging. Indeed, proteostasis pathways, such as the heat shock response and aggregation of metastable proteins, are also controlled by thermosensory neurons in C. elegans. Prolonged heat stress is thought to play a critical role in the development of neurodegenerative protein misfolding diseases in humans. This review presents the latest evidence on how temperature coordinates proteostasis and aging. It also discusses how studies of poikilothermic organisms can be applied to vertebrates and provide new therapeutic strategies for human disease.